The nature of Death in Emily Dickinson’s, William Sommerset Maughm, and John Donne: A Dialogism Analysis - Ukhrowi, Wim Banu (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
A literary work comes with its own uniqueness. It has given big contribution to the literature development since centuries years ago. From some literary works, we have the portrait of the society or the condition arose in the past time. Surprisingly in some literary works sometimes we can find there is such a good relationship between one literary work and other literary work. It can be in the form of the issues brought by the writer or the setting of the story although (sometimes) between the writers do not know each other. A good relationship, in this case the similarities emerged in one literary work and another literary work as so called intertextuality. Intertextuality bridges the literary works. This short research tries to find out the intertextuality based on dialogism theory emerged by Mikhail Bahtim in three literary works. They are the work of Emily Dickinson entitled Because I Could Not Stop for Death, a work as retold by William Sommerset Maughm entitled Appointment in Samarra and one literary work by John Donne with the title Death, be not proud.. It has been found that the term death could be portrayed in many different ways. In a work by Emily Dickinson, the death was figured out as a male. In Appointment in Samarra, the detah came as a female while in Death, Be not proud, the death showed unclearly in term og gender whether it is male or female. In term of the power issue. The three literary works also depicted in various ways. The death figure was shown as the less power toward the main character in appointment in Samarra. The power issue in Death, Be not proud, the death was figured out as a character who had more power while in Because I could not stop for death, the death character shown in more powerful comparing to the speaker.